Cognitively unimpaired individuals with a low burden of Aβ pathology have a distinct CSF biomarker profile - Milà-Alomà, Marta; Shekari, Mahnaz; Salvadó, Gemma; Gispert, Juan Domingo; Arenaza-Urquijo, Eider M.; Operto, Grégory; Falcon, Carles; Vilor-Tejedor, Natalia; Grau-Rivera, Oriol; Sala-Vila, Aleix; Sánchez-Benavides, Gonzalo; González-de-Echávarri, José Maria; et al. (Alzheimer's research & therapy, 2021)
Background Understanding the changes that occur in the transitional stage between absent and overt amyloid-β (Aβ) pathology within the Alzheimer’s continuum is crucial to develop therapeutic and preventive strategies. The objective of this study is to test whether cognitively unimpaired individuals with a low burden of Aβ pathology have a distinct CSF, structural, and functional neuroimaging biomarker profile. Methods Cross-sectional study of 318 middle-aged, cognitively unimpaired individuals from the ALFA+ cohort . We measured CSF Aβ42/40, phosphorylated tau (p-tau), total tau (t-tau), neurofilament light (NfL), neurogranin, sTREM2, YKL40, GFAP, IL6, S100B, and α-synuclein. Participants also underwent cognitive assessments, APOE genotyping, structural MRI, [ 18 F]-FDG, and [ 18 F]-flutemetamol PET. To ensure the robustness of our results, we used three definitions of low burden of Aβ pathology: (1) positive CSF Aβ42/40 and < 30 Centiloids in Aβ PET, (2) positive CSF Aβ42/40 and negative Aβ PET visual read, and (3) 20–40 Centiloid range in Aβ PET. We tested CSF and neuroimaging biomarker differences between the low burden group and the corresponding Aβ-negative group, adjusted by age and sex. Results The prevalence and demographic characteristics of the low burden group differed between the three definitions. CSF p-tau and t-tau were increased in the low burden group compared to the Aβ-negative in all definitions. CSF neurogranin was increased in the low burden group definitions 1 and 3, while CSF NfL was only increased in the low burden group definition 1. None of the defined low burden groups showed signs of atrophy or glucose hypometabolism. Instead, we found slight increases in cortical thickness and metabolism in definition 2. Conclusions There are biologically meaningful Aβ-downstream effects in individuals with a low burden of Aβ pathology, while structural and functional changes are still subtle or absent. These findings support considering individuals with a low burden of Aβ pathology for clinical trials. Trial registration NCT02485730